A case report on Anaesthesia and Ventriculo-Peritoneal Shunt with Hydrocephalus - Yilkal Tadesse Desta (Global Journal of Perioperative Medicine - Peertechz Publications, 2022)
Childhood hydrocephalus is a common disorder in which too much Cerebrospinal Fluid (CSF) accumulates within the ventricles (fluid-containing spaces) of the brain and is usually the-ted by cerebrospinal fluid shunting using a ventriculoperitoneal or ventriculoarterial shunts. The most common condition is hydrocephalus, where there is dilation of the ventricular system due to an obstruction in the flow of CSF or decreased absorption of CSF by the arachnoid villi. Shunting of CSF is the treatment of choice in childhood hydrocephalus.